Studi meta-analisis implementasi model pembelajaran inkuiri untuk meningkatkan kemampuan pemecahan masalah matematis siswa - Sembadha, Rinomulat; Gunawan, Iwan; Budilestari, Puji (Jurnal Pendidik Indonesia, 2022)
This study addressed the problem that the amount of further study made to see the correlation between inquiry learning and mathematical problem solving more thoroughly was barely minimum. Therefore, the researcher used meta-analysis, which analyzed this cause from a general point of view and three partial points of view; grade, location, and field of study. The population of this study was all the pedagogic publications which included inquiry learning as an independent variable and mathematical problem solving as a dependent variable in the span of 2015-2020. The researcher found 14 articles from several portals, but only seven meet the requirements for calculating the effect size. The result showed that the average effect size could be interpreted as the medium. From a partial point of view, grade VIII had a better effect size, cities in which students scored better on national mathematic assessments had a tendency for better effect size, and Algebra was the field of study with a better effect size.